Table of Content - - (Journal of Islamic Sciences, 2025)
Table of Content: 1. Love in the Islamic Religion Dr. Mohammed Remedan Yusuf 2. The effects of the phenomenon of extremism on intellectual security Dr. Majed Marzoug Al-Harbi 3. Abortion between Islamic provisions and a criminal crime Asst-lecturer Maad Dhaeer Naeem 4. Smoke and Vapor of Najāsah Between Fiqh and Chemistry: An Analytical Jurisprudential Study Dr. Musatafa Muhammad Karakira